Penggunaan Akun TikTok @Hudzaa Dalam Pemenuhan Pengetahuan Agama Followers - Soniari Valentina Damanik; Winda Kustiawan (Akademika, 2023)
Social media can affect people's mindset and lifestyle, especially millennials. From various information obtained on social media, one of them that can be applied is da'wah activities. This research uses a social media case study, namely the Tiktok application conducted by Hafiz Qur'an, and a young da'i, the Tiktok account @Hudzaa. The case study in this study is that followers of Tiktok accounts @Hudzaa. Research method, using qualitative methods with a descriptive approach and interviews with followers. The purpose of this study is to find out whether there is an influence of the @Hudzaa tiktok account on the effectiveness of da'wah for followers. The study's results, the use of TikTok @Hudzaa as a da'wah medium is appropriate, and a short drama in da'wah has a positive impact on followers, so followers have applied it in everyday life. It is hoped that this research can be a new insight for the millennial generation and in creating content on the Tiktok application to be more innovative in delivering da'wah in accordance with the challenges of the times.